Synthesis and Transforming of 3-cyclohexyl-4-formylsydnone N-(2’,3’,4’,6’-tetra-O-acetyl-β-D glucopyranosyl)thiosemicarbazone Compound from Cyclohexylamine - Duc, Hoang Thanh; Thanh, Nguyen Dinh (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 2DO - 10.25073/2588-1140/vnunst.4753, 2018)
The thiosemicarbazone compound ( 6 ) contains sydnone ring, was synthesized from 4-formylsydnone ( 4 ), derived from cyclohexylamine ( 1 ), via four reaction series, by microwave irradiation method with 85%-yield. From the thiosemicarbazone compound ( 6 ), we performed cyclization reaction of thioure group with ethyl bromoacetate, in ethanol solvent and sodium acetate catalyst for 46 hrs to obtain thiazolidine-4-one ( 7 ) with 68%-yield. Cyclization reaction of imine group with acetic anhydride, in dichloromethane solvent for 48 hrs gave 4,5-dihydro-1,3,4-thiadiazole compound ( 8 ) with 60%-yield. Complex-formation reaction of thiosemicarbazone ( 6 ) with zinc acetate at room temperature, in a solvent of ethanol, for 3 hours yielded bis[thiosemicarbazonato]zinc(II) complex ( 9 ) with 80%-yield. Structures of thiosemicarbazone derivatives ( 6 ), thiazolidin-4-one ( 7 ), 4,5-dihydro-1,3,4-thiadiazole ( 8 ) and bis[thiosemicarbazonato]zinc(II) complex ( 9 ) was confirmed by modern spectroscopic methods (IR, 1 H & 13 C NMR and MS).  Keywords Thiosemicarbazone, thiazolidin-4-one, 1,3,4- thiadiazole References [1]. Alaa A. H., Ahmed M. S., and Hamdy S. “Chemistry and Heterocyclization of Thiosemicarbazones”, Journal of Heterocyclic Chemistry Vol. 49, pp. 21- 37 (2012). [2]. Altun Ah., Kumru M., Dimoglo A. “Study of electronic and structural features of thiosemicarbazon and thiosemicarbazid derivatives demonstrating anti-HIV-1 activity”, Journal Molecular Structure Chem Vol. 535, pp. 235-246 (2001). [3]. Belicchi F.M., Bisceglie F., Pelosi G., Tarasconi P., Albertini R. and Pinelli S. “New methyl pyruvate thiosemicarbazones and their copper and zinc complexes: synthesis, characterization, X-ray structures and biological activity”, Journal of Inorganic Biochemistry Vol. 87(3), pp. 137-147 (2001). [4]. Browne D. L., Harrity J. P. A. “Recent developments in the chemistry of sydnones”, Tetrahedron, report number 897 Vol. 66, pp. 553-568 (2010). [5]. Dunkley C. S., Thoman C. J. “Synthesis and biological evaluation of a novel phenyl substituted sydnone series as potential antitumor agents”, Bioorganic Medicinal Chemistry Letters Vol. 13, pp. 2899-2901 (2003). [6]. Diaz A., Cao R., and Garcia A. “Characterization and biological properties of a copper (II) complex with pyruvic acid thiosemicarbazon”, Monatshefte fur Chemie/ Chemical Monthly Vol. 125(8-9), pp. 823-825 (1994). [7]. Mei-Hsiu S., Fang-Ying K. “Syntheses and evaluation of antioxidant activity of sydnonyl substituted thiazolidinone and thiazoline derivatives”, Bioorganic Medicinal Chemistry Vol. 12, pp. 4633-4643 (2004). [8]. Hoàng Thanh Đức. Tổng hợp và tính chất của các hợp chất 4-acetyl và 4-formylsydnone (per-O-acetyl-β-D-glycopyranosyl) thiosemicarbazon, Luận án tiến sỹ Hoá học, trường Đại học Khoa học tự nhiên (ĐHQG Hà Nội), Hà Nội, (2015). [9]. Nguyen Dinh Thanh, Hoang Thanh Duc, Vu Thi Duyen “Study on synthesis of some 3-aryl-4-formylsydnone 4-(tetra-O-acetyl-β-D-glucopyranosyl)thiosemicarbazones”, Tạp chí Hoá học, T. 51 (No.5A), tr. 32-37 (2013). [10]. Li Y. X., Wang S. H., Li Z. M. “Synthesis of novel 2-phenyl sulfonylhydrazono-3-(2’,3’,4’,6’-tetra-O-acetyl-β-D-glucopranosyl) thiazolidine-4-ones from thiosemicarbazide precursors”, Carbohydrate Research 341, pp. 2867-2870 (2006). [11]. Mei-Hsiu S., Fang-Ying K. “Syntheses and evaluation of antioxidant activity of sydnonyl substituted thiazolidinone and thiazoline derivatives”, Bioorganic Medicinal Chemistry Vol. 12, pp. 4633-4643 (2004). [12]. Mei-Hsiu S., Cheng-Ling W. “Efficient syntheses of thiadiazoline and thiadiazole derivatives by the cyclization of 3-aryl-4-formylsydnone thiosemicarbazones with acetic anhydride and ferric chloride”, Tetrahedron Vol. 61, pp. 10917-10925 (2005).